Board Structure and Bank Performance: Evidence for the Greek Banking Industry during Crisis Period - Andreas G. Georgantopoulos; Ioannis Filos (International Journal of Economics and Financial Issues, 2017)
The recent financial crisis has heightened the research interest worldwide in the relationship between various corporate governance mechanisms and firm performance. Nevertheless, few published papers focus on investigating this nexus for the case of the banking industry. This study is the first that empirically assesses the impact of board structure on bank performance for the case of Greek banks using a variety of econometric methodologies. Exhaustive empirical findings are presented based on a sample of thirteen Greek banks and for a period of severe sovereign debt crisis (2008-2014). Empirical findings support an inverted U-shaped relation between board size and bank performance and between the proportion of independent board members and performance of Greek banks. All empirical findings are generated after we control for M&A activity, bank size and capital adequacy of each bank. Overall, our results document the positive contribution of the implemented corporate governance regulatory framework on the Greek bank value.